Predictors of batting and pitching performance in the USA baseball prospect development pipeline - Feng, Z.; Lochhead, L.; Kohn, J. N.; Appelbaum, L. G. (Sports Biomechanics, 2025)
This study examined the relationship between psychomotor abilities and baseball performance by analysing data from 379 athletes who participated in the USA Baseball, Prospect Development Pipeline (PDP). Hit and pitch metrics were generated during practice sessions using the RapsodoTM System. Data were compared through exploratory factor analysis and hierarchical regression. Factor analysis grouped batter`s PDP evaluations into four latent variables accounting for 63% of variance. Pitcher performance grouped into three factors accounting for 51% of variance. Regression on batter data revealed a significant demographic/anthropometric base model with height, weight, and age that accounted for 58% of the batted ball speed (R2 = 0.581). Player position explained 2% of the variance (R2 = 0.604), and PDP evaluation scores contributed an additional 3% (R2 = 0.631). Regression of pitcher data showed a significant base demographic/anthropometric model accounting for 36% of fastball pitch speeds (R2 = 0.363), with the PDP evaluation scores adding 6% additional variance (R2 = 0.424). Uniformly, assessments of lower body strength added the greatest predictive information. Hand grip strength did not correlate with pitch metrics. While demographics/anthropometrics are major contributors to batted and pitched ball speed, position and psychomotor variables add statistically significant contributions and may be of practical value for player selection.